Can intensification reduce emission intensity of biofuel through optimized fertilizer use? Theory and the case of oil palm in Indonesia. Issue 5 (2nd December 2016) - van Noordwijk, Meine; Khasanah, Ni'matul; Dewi, Sonya
Abstract: Closing yield gaps through higher fertilizer use increases direct greenhouse gas emissions but shares the burden over a larger production volume. Net greenhouse gas (GHG) footprints per unit product under agricultural intensification vary depending on the context, scale and accounting method. Life cycle analysis of footprints includes attributable emissions due to (i) land conversion ('fixed cost'); (ii) external inputs used ('variable cost'); (iii) crop production ('agronomic efficiency'); and (iv) postharvest transport and processing ('proportional' cost). The interplay between fixed and variable costs results in a nuanced opportunity for intermediate levels of intensification to minimize footprints. The fertilizer level that minimizes the footprint may differ from the economic optimum. The optimization problem can be solved algebraically for quadratic crop fertilizer response equations. We applied this theory to data of palm oil production and fertilizer use from 23 plantations across the Indonesian production range. The current EU threshold requiring at least 35% emission saving for biofuel use can never be achieved by palm oil if produced: (i) on peat soils, or (ii) on mineral soils where the C debt due to conversion is larger than 20 Mg C ha −1, if the footprint is calculated using an emission ratio of N2 O–N/N fertilizer of 4%. At current fertilizer price levels in Indonesia, the economically optimized N fertilizer rate is 344–394 kg N ha −1, while the reported mean N fertilizer rate is 141 kg N ha −1 yr −1 and rates of 74–277 kg N ha −1 would minimize footprints, for a N2 O–N/N fertilizer ratio of 4–1%, respectively. At a C debt of 30 Mg C ha −1, these values are 200–310 kg N ha −1 . Sustainable weighting of ecology and economics would require a higher fertilizer/yield price ratio, depending on C debt. Increasing production by higher fertilizer use from current 67% to 80% of attainable yields would not decrease footprints in current production conditions. Abstract : Simple field methods for quantifying the carbon stocks in oil palm plantations contribute data to the calculated footprint of palm oil in response to N fertilizer rates.